Comparison of promoter, DNA vector, and cationic carrier for efficient transfection of hMSCs from multiple donors and tissue sources - Tyler Kozisek; Andrew Hamann; Luke Samuelson; Miguel Fudolig; Angela K. Pannier (Elsevier, 2021)
Human mesenchymal stem cells (hMSCs) are primary cells with high clinical relevance that could be enhanced through genetic modification. However, gene delivery, particularly through nonviral routes, is inefficient. To address the shortcomings of nonviral gene delivery to hMSCs, our lab has previously demonstrated that pharmacological "priming" of hMSCs with clinically approved drugs can increase transfection in hMSCs by modulating transfection-induced cytotoxicity. However, even with priming, hMSC transfection remains inefficient for clinical applications. This work takes a complementary approach to addressing the challenges of transfecting hMSCs by systematically investigating key transfection parameters for their effect on transgene expression. Specifically, we investigated two promoters (cytomegalovirus [CMV] and elongation factor 1 alpha), four DNA vectors (plasmid, plasmid with no F1 origin, minicircle, and mini-intronic plasmid), two cationic carriers (Lipofectamine 3000 and Turbofect), and four donors of hMSCs from two tissues (adipose and bone marrow) for efficient hMSC transfection. Following systematic comparison of each variable, we identified adipose-derived hMSCs transfected with mini-intronic plasmids containing the CMV promoter delivered using Lipofectamine 3000 as the parameters that produced the highest transfection levels. The data presented in this work can guide the development of other hMSC transfection systems with the goal of producing clinically relevant, genetically modified hMSCs.